Menggali Potensi Lokal Berbasis Pancasila: Pelatihan Pembuatan Stik Bawang Merah Bersama Ibu-Ibu PKK Di Desa Tugu Lor - Amnan Haris; Muhamad Iqbal Hadi; Fernanda Ade Yusuf; Maha Mardhatilla; Naraendra Pramudita (Jurnal Bina Desa, 2026)
This community service activity aims to empower women in Tugu Lor Village as Pancasila agent women through training in making red onion sticks. By utilizing the local potential of red onion, this training is expected to increase the added value of the product, empower the community's economy, and strengthen the values of Pancasila and implement it into various aspects of daily life. The object used in this activity is red onions as a local superior product of Tugu Lor Village into brown sugar stik. The method used is socialization and training based on theory and practice by actively involving PKK mothers. The service results obtained from this activity are increasing the skills and knowledge of PKK women in processing brown sugar into high-value products. In addition, this training also succeeded in strengthening the understanding and application of Pancasila values in everyday life. This service concludes that empowering women through productive economic activities can be one of the strategies to reduce the gender gap and improve the quality of life of the community.